Hedging with a generalised basis risk: empirical results. (19th September 2011) - Alghalith, Moawia; Lalloo, Ricardo; Franklin, Martin; Floros, Christos
Previous research assumes that Using a general form of basis risk, we provide empirical comparative statics results. Moreover, we relax the statistical independence assumption. Our monthly data series covers the period March 2000 to 2010, and includes the Henry Hub spot price, futures price and the quantity of natural gas and the hedged quantity. The results show that